LOCAL GOVERNMENTS FINANCIAL REPORTING QUALITY IN PAPUA AND WEST PAPUA: DO LOCAL GOVERNMENT CHARACTERISTICS MATTER? - Amrie Firmansyah; Zef Arfiansyah; Muhamad Rizal Yuniar (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2022)
This study investigates the effect of local government size, local government spending, and the local government dependence level on the financial reporting quality. This study employs a quantitative method. The research data summarizes the financial statements of the regency/city governments in Papua and West Papua from 2016 to 2020. The data is sourced from www.djpk.kemenkeu.go.id and www.bpk.go.id. By using purposive sampling, the sample amounted to 207 observations. The hypothesis testing of this research was conducted employing logistic regression. The test results suggest that the local government size and local government spending are positively associated with financial reporting quality. In contrast, the local government dependence level is negatively associated with financial reporting quality.